THE INFLUENCE OF SCIENCE LEARNING QUALITY IN THE SCHOOL THROUGH SCIENCE LEARNING OUTCOME INDONESIAN STUDENTS BASED ON PISA STUDIES 2015 - Purwo - Susongko (EDUSAINS, 2018)
PENGARUH KUALITAS PEMBELAJARAN SAINS DI SEKOLAH MELALUI CAPAIAN PEMBELAJARAN SAINS SISWA INDONESIA BERDASARKAN PISA STUDI 2015 AbstractThis research aims to understand: (1) factors for indicators in science learning outcome of Indonesian students based on PISA studies in 2015, (2) factors for indicators of science learning quality Indonesian students based on PISA studies 2015, (3) the influence of learning quality through science learning outcome Indonesian students based on  grade achievement school. This study uses ex-post facto research method. Data analyze technique uses Structural Equation Modelling (SEM). There are 6,425 student they are 1,208 student from high grade achievement school, 4,005 student from intermediete grade achievement school and 1,212 student from low grade achievement school. Research result shows: (1) Environment awareness, Enjoyment of science, Instrumental motivation, Science Self-Efficacy, Epistemological  beliefs, and Science Achievement  are valid indicators from science learning outcome Indonesian students based on PISA survey in 2015, (2) Teacher support in a science classes of students choice, Inquiry-based instruction  in science lesson, Teacher-directed science instruction and Perceived Feedback are valid indicators from science learning quality Indonesian students b.ased on PISA studies 2015, (3) In high grade achievement school, the quality of learning had 0.31 influences to sicence learning outcome Indonesian students with determination level of 10%, (4) In intermediete grade achievement school, the quality of learning had 1 influences to science  learning outcome Indonesian students with determination level of 100%, (5) In low grade achievement school, the quality of learning had 0.51 influences to sicence learning outcome Indonesian students with determination level of 26%.AbstrakPenelitian ini bertujuan untuk memahami: (1) faktor indikator hasil belajar sains siswa Indonesia berdasarkan studi PISA tahun 2015, (2) faktor indikator kualitas pembelajaran sains siswa Indonesia berdasarkan studi PISA tahun 2015, (3) Pengaruh kualitas pembelajaran terhadap capaian pembelajaran sains siswa Indonesia berdasarkan tingkat prestasi belajarnya. Penelitian ini menggunakan metode penelitian ex-post facto. Teknik analisis data menggunakan Structural Equation Modeling (SEM). Ada 6.425 siswa yang terdiri 1.208 siswa dari sekolah prestasi tingkat tinggi, 4.005 siswa dari sekolah pencapaian kelas menengah dan 1.212 siswa dari sekolah prestasi kelas rendah. Hasil penelitian menunjukkan: (1) Environment awareness, enjoyment of Science , Instrumental motivation, Science Self-Efficacy, Epistemological  beliefs, dan  Science Achievement  merupakan  indikator yang valid dari capaian pembelajaran sains siswa Indonesia berdasarkan survai PISA 2015, (2) Teacher support in a science classes of students choice ,   Inquiry-based instruction  in science lesson , Teacher-directed science instruction dan Perceived Feedback merupakan indikator yang valid dari kualitas pembelajaran sains siswa Indonesia berdasarkan studi PISA 2015, (3) Pada sekolah prestasi kelas tinggi, kualitas pembelajaran memiliki 0,31 pengaruh terhadap kemahiran hasil belajar siswa Indonesia dengan tingkat determinasi 10%, (4) Pada sekolah pencapaian kelas menengah, kualitas pembelajaran memiliki 1 pengaruh terhadap hasil belajar sains siswa Indonesia dengan tingkat determinasi 100%, (5 ) Pada sekolah dengan prestasi belajar rendah   kualitas pembelajaran berpengaruh sebesar 0.51 terhadap capaian pembelajaran sains siswa  Indonesia dengan taraf determinasi sebesar 26 %.